The Investigation of Electric Scooter Accident Cases Admitted to the Emergency Department: A Multicenter Study - Kılıç, Serbülent; Yüksel, Melih; Şahin, Musa; Oto, Arzu; Eraybar, Suna; Durak, Vahide Aslıhan; Cander, Sümeyye Tuğba Sarkı (Lycia Press London UK, 2023)
Objective: Electric scooters are a new form of inner-city transportation, which is considered to be an accessible, affordable, and popular option within society. Aims: This study aimed to describe the demographic and clinical characteristics of individuals involved in electric scooter accidents and the factors associated with these incidents. Methods: We conducted a prospective observational study of individuals involved in electric scooter crashes presented to the emergency department of four hospitals in Bursa/Turkey. Those hospitals were divided into two groups as Impoverished Region (IR) and Wealthy Region (WR). Sixty-two individuals who sustained ESA and were admitted to the ED of the four hospitals involved in our study from the start date 11/08/2022 till the end date of  11/012/2022. Results: A total number of 62 patients (24 females, 38 males) sustained electric scooter related injuries. The most commonly seen injury patterns were abrasion (n=42, 67.7%), soft tissue injury (n=27, 43.5%), and bone fracture (n=11, 17.7%), respectively. The lower and upper limbs and head injuries were the most commonly seen injury sites. Injury of the head (p=0.000), injury of the lower extremity (p=0.0230), injury of the upper extremity (p=0.004), and injury of trunk (p=0.008), were significantly associated with multiple injuries. Loss of balance was the most frequent ESA cause (n=43, 69.4%) followed by a hit to a stable object (n=11, 17.7%) Conclusions: Our study revealed that electric scooter accidents occurred in the initial moments of driving in low-income regions of the city compared to the wealthy areas. Head/neck injuries are more likely to occur in children in those cases
Keywords: 11. Sustainability; 3. Good health